1978
DOI: 10.1161/01.res.43.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Clonal markers in the study of the origin and growth of human atherosclerotic lesions.

Abstract: The X-linked enzyme, glucose-6-phosphate dehydrogenase (G-6-PD) was used as a cellular marker to study the clonal characteristics of human atherosclerotic lesions from females heterozygous for G-6-PD isoenzymes. Portions of uninvolved aortic wall contained both isoenzyme types (A and B), and their isoenzyme patterns were used to establish criteria for polyclonal lesions. Portions of uterine leiomyomas contained predominantly one isoenzyme type (either all A or all B) and their isoenzyme patterns were used to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
0

Year Published

1983
1983
2003
2003

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…Previous observations that a single phenotype for SMC made up a significant proportion of atherosclerotic fibrous plaques suggested the possibility that they are a form of benign neoplasm in the arterial intima (4)(5)(6)10). This view has been disputed largely on the basis of experimental animal models of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous observations that a single phenotype for SMC made up a significant proportion of atherosclerotic fibrous plaques suggested the possibility that they are a form of benign neoplasm in the arterial intima (4)(5)(6)10). This view has been disputed largely on the basis of experimental animal models of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Intimal smooth muscle cell (SMC) proliferation is regarded as a key early event in the pathogenesis of atherosclerosis (1)(2)(3). Cell lineage analysis of human atheromata, using X-linked glucose-6-phosphate de-hydrogenase isozymes as markers, revealed that the cell population of many lesions consisted of a single phenotype, in sharp contrast to the normal artery wall and diffusely thickened intima (4)(5)(6). These results are indicative of an unusual proliferative response and are similar to data obtained from analyses of cell origins of benign smooth muscle tumors of the uterus (7,8).…”
mentioning
confidence: 99%
“…It has been suggested that such monoclonal populations could arise consequent to endothelial cell injury (25), perhaps secondary to differential growth responses to platelet or mononuclear cell derived growth mediators.…”
Section: Discussionmentioning
confidence: 99%
“…This possibility has been raised on the basis of original work by Benditt and Benditt,4 who reported that human atheromatous plaques have the features of a monoclonal lesion, an observation that has been confirmed by several laboratories. [5][6][7] More recently, with use of in situ microdissection techniques, it has been demonstrated that human plaques are at least oligoclonal. 8 These findings support the suggestion that SMCs of the arterial wall are biologically heterogeneous, and thus, attempts have been made to isolate distinct SMC phenotypes from arterial vessels.…”
mentioning
confidence: 99%